Functionally characterization of the most common LDLR missense alterations found in Portuguese FH patients - Alves, A.C. (2018)
Aims: Mutations in the LDLR gene are the major cause of familial hypercholesterolaemia (FH), which results in defective catabolism of LDL leading to premature coronary heart disease. Presently, more than 1700 different mutations in the LDLR gene have been described as causing FH but the majority of them remain without functional characterization. In the Portuguese Familial Hypercholesterolemia Study (PFHS), 123 LDLR alterations were found in 243 index patients and their relatives up to date. Until now, 70 of these alterations already have a final classification of pathogenic and 15 have been proved by in vitro studies to be non-pathogenic. The aim of the present work is to functionally characterize 16 LDLR missense alterations found in Portuguese FH patients and worldwide.